Open Inquiry Practicum: An Effective Strategy for Enhancing Science Process Skills of Prospective Biology Teachers - Muhlis Muhlis; I Wayan Merta; AA Sukarso; Gito Hadiprayitno; I Putu Artayasa (Jurnal Penelitian Pendidikan IPA, 2023)
Practicum has been widely recognized as an effective approach to enhance science process skills. However, traditional practicums may not be sufficient in improving integrated process skills. To address this issue, the current study aimed to introduce the open inquiry practicum model and investigate its impact on basic and integrated process skills among prospective biology teacher students. The study was conducted during the odd semester of 2022-2023, where selected courses utilized practicums both in and outside of the laboratory to facilitate open inquiry learning. A quasi-experimental study with a non-equivalent control group design was conducted to assess the effect of open inquiry practicum on students' science process skills. Data was collected from observing the practicum process utilizing the open inquiry learning model, as well as pretest and posttest results of science process skills. Treatment effect was analyzed through Mann-Whitney test with an alpha level of 0.05. The open inquiry practicum model consisted of experimental design preparation, practical field and laboratory work, data collection and analysis, data presentation, and uploading practical activity products in the form of posters and videos to YouTube. The results indicated a significant improvement in students' science process skills through the implementation of the open inquiry practicum.